TOWARDS A STRATEGY FOR SAFETYORIENTED URBAN STRUCTURE - Irina Matijosaitiene; Inga Stankevice (European Scientific Journal, ESJ, 2015)
The paper represents analysis and modelling of urban spaces through their topological properties in order to make them safer in terms of robberies, larceny and motor vehicle thefts, stolen properties, weapons and drugs. The research is performed on a macro-scale in the city of New Haven, Connecticut, USA. The topological properties of streets were calculated and analyzed by the application of space syntax method and DepthMap software, GIS and SPSS. The results are explained in the terms of people movement and presence on the main streets which are on the natural search paths of possible criminals, and which on the other hand have been assigned to a greater surveillance effect from movement.